Kinetics of Plasma Cytokines, Angiopoietin-2, and C-Reactive Protein in Dogs With Gastric Dilatation Volvulus - Brunner, Anna; Schuller, Simone; Hettlich, Bianca; Marti, Eliane; Lehmann, Anna; Peters, Laureen M.; Adamik, Katja-Nicole (Frontiers in Veterinary Science, 2021)
Background: The degree of systemic inflammation, reperfusion injury and endothelial activation are potentially important determinants of clinical outcomes in dogs with gastric dilatation volvulus (GDV). Objective: To evaluate plasma concentrations and kinetics of inflammatory markers in dogs with GDV over a time frame of 48 hours, and to compare to healthy dogs. Design and setting: Prospective, observational cohort study in client-owned dogs with GDV. Materials and Methods: Fifteen dogs with GDV and 9 healthy control dogs were enrolled. Plasma concentrations of interleukin (IL)-6, IL-7, IL-8, IL-10, IL-15, IL-18, interferon gamma (IFN-), keratinocyte chemotactic-like, monocyte chemotactic protein (MCP) -1, Angiopoietin (Ang)-2, and C-reactive protein (CRP) were measured at admission (prior any therapeutic intervention, T0), immediately after surgery (T1), 24  4 hours (T24), and 48  4 hours (T48) post-surgery. Cytokines were measured using multiplex magnetic bead assay. Plasma Ang-2 was measured with a commercial human ELISA test kit validated for dogs. Results: Dogs with GDV had significantly higher plasma concentrations of IFN- and IL-10 compared to healthy control dogs at all time points. Concentrations of IL-6 were significantly higher at T1 and T24, concentrations of MCP-1 at T24, and concentrations of CRP at T24 and T48. A significant increase between T0 and T1 was found for IL-6, IL-10, and CRP, between T1 and T24 for IL-8, IFN-, MCP-1, and CRP, and between T24 and T48 for IL-15, Ang-2, and CRP. A significant decrease between T0 and T1 was found for IL-7, IL-8, IL-15, IL-18, and Ang-2; between T1 and T24 for IL-6 and KC-like; and between T24 and T48 for IL-6. Conclusion: In GDV dogs, a mild pro-inflammatory reaction was present at admission, which peaked immediately after and up to 24 hours post-surgery, mainly represented by IL-6, IFN-, MCP-1, and CRP, and which decreased at T48. In addition, the anti-inflammatory IL-10 was increased in GDV dogs at all time points.